PENGARUH GAME: PES 2013 TERHADAP KEMAMPUAN PENYERAPAN PEMAHAMAN PERATURAN PERMAINAN SEPAKBOLA (STUDI PADA MAHASISWA PENDIDIKAN OLAHRAGA ANGKATAN 2012 UNIVERSITAS NEGERI SURABAYA) - AZWAR ANNAS, MUHAMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Consol game have already being a prime on entertainment worldwide nowday. In spite of have long time to make a difference but just recently being the most important choice for a solace or holiday. Education world-section had starting to make a learning using an audio visual media. But in this time, especially in physical education, have not using yet this consol game for media learning. Whereas, practically, almost all students wasting their time just for play this game. Together with football game popularity progress, particularly PES 2013, every people getting easy to knowing and understanding everything inside of this game. Start from kind of competition, competition system, and laws of the game. But in fact, a lot of people, particularly student of physical education could not caught a chance of this game as a bridge to knowing deeply about the law of the game. The purpose of this research is to knowing how many informations, knowledges, and comprehensions about the law of football game that could absorbed by student of physical student 2012 in University State of Surabaya using PES 2013 game, with 20 amount of samples. Based on research have done, that PES 2013 applied can make greater effect for comprehension of laws of the football game ability, rising point is about 54,85%. Keywords : Game PES 2013, comprehension absorb the law of football game ability.